2012
DOI: 10.1111/mmi.12054
|View full text |Cite|
|
Sign up to set email alerts
|

Natural competence in Vibrio cholerae is controlled by a nucleoside scavenging response that requires CytR‐dependent anti‐activation

Abstract: SummaryCompetence for genetic transformation in Vibrio cholerae is triggered by chitin-induced transcription factor TfoX and quorum sensing (QS) regulator HapR. Transformation requires expression of ComEA, described as a DNA receptor in other competent bacteria. A screen for mutants that poorly expressed a comEAluciferase fusion identified cytR, encoding the nucleoside scavenging cytidine repressor, previously shown in V. cholerae to be a biofilm repressor and positively regulated by TfoX, but not linked to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 81 publications
(179 reference statements)
3
87
0
Order By: Relevance
“…By this hypothesis, a depletion of nucleoside pools signals DNA uptake, while an excess of nucleosides halts competence. In V. cholerae, recent evidence linking nucleoside uptake to competence bolsters such an argument and is described below (13).…”
Section: Nucleoside Sensing Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…By this hypothesis, a depletion of nucleoside pools signals DNA uptake, while an excess of nucleosides halts competence. In V. cholerae, recent evidence linking nucleoside uptake to competence bolsters such an argument and is described below (13).…”
Section: Nucleoside Sensing Systemmentioning
confidence: 99%
“…Liang et al demonstrated in El Tor strain C7258 that Δcrp mutants are reduced for transcription of the major autoinducer synthase gene cqsA (14). As both A1552 and C6706 ΔcqsA mutants are defective in DNA uptake (12,13), one effect of CRP on competence likely also includes modulation of QS (Fig. 2).…”
Section: Grammentioning
confidence: 99%
See 3 more Smart Citations